2020
DOI: 10.2196/21845
|View full text |Cite
|
Sign up to set email alerts
|

Communication Technology Preferences of Hospitalized and Institutionalized Frail Older Adults During COVID-19 Confinement: Cross-Sectional Survey Study

Abstract: Background Technological communication methods such as telephone calls and video calls can help prevent social isolation and loneliness in frail older adults during confinement. Objective Our objectives were to determine which virtual communication method (ie, telephone call or video call) was preferred by confined older hospital patients and nursing home residents and the variables influencing this preference. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(108 citation statements)
references
References 20 publications
1
100
0
1
Order By: Relevance
“…However, their use remains variable and less widespread among older adults [ 32 ], and prior research has reported risks associated with health information tracking, which may trigger negative emotions among patients with multiple chronic conditions and potential emotional draining in this group [ 33 ]. With the current COVID-19 crisis, calls for initiatives and efforts to bridge health information and communication technologies with the care for older adults have appeared in various countries as a preparedness mechanism and a mitigating approach against the current and future pandemics [ 7 , 10 , 34 , 35 ]. However, to date, limited information is available on older adults’ attitudes toward and their use of mHealth technologies for self-tracking purposes—an area that reveals to be increasingly important during and following this COVID-19 era.…”
Section: Introductionmentioning
confidence: 99%
“…However, their use remains variable and less widespread among older adults [ 32 ], and prior research has reported risks associated with health information tracking, which may trigger negative emotions among patients with multiple chronic conditions and potential emotional draining in this group [ 33 ]. With the current COVID-19 crisis, calls for initiatives and efforts to bridge health information and communication technologies with the care for older adults have appeared in various countries as a preparedness mechanism and a mitigating approach against the current and future pandemics [ 7 , 10 , 34 , 35 ]. However, to date, limited information is available on older adults’ attitudes toward and their use of mHealth technologies for self-tracking purposes—an area that reveals to be increasingly important during and following this COVID-19 era.…”
Section: Introductionmentioning
confidence: 99%
“…First, from the policy perspective, based on the experience of the COVID-19 pandemic, policy makers should be driven toward developing a contingency plan that includes strategies of promotion and regulation of web-based medical services by defining the scopes and standards as well as the rights and responsibilities of the entities [23]. Secondly, from the implementation perspective, hospitals should plan ahead for the establishment of internet hospitals in accordance with local conditions, establish digital health technologies, and formulate emergency response measures against severe infectious disease outbreaks [24]. However, there is no "one-size-fits-all" strategy for all hospitals; the functionalities should be tailored to each hospital's needs, and the available tools should be shared within the medical consortium to achieve the highest cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…These provide good initiatives to increases the chances to fulfil the aim of equal health care for all. All dentistry devices and instruments are easily connected through internet applications, sharing data for better communication [ 55 , 56 ]. All medical and fitness-related activities are shared quickly through the Internet of Dental Things.…”
Section: Digital Dentistry Using Dentistry 40 Technologiesmentioning
confidence: 99%